Concept of Islamic Religious Education learning Material Development In Majelis Ta'lim Through A Holistic-Integralistic Approach - Zulkifli , Zulkifli; Alfitri , Alfitri; Mohamad Abdun Nasir (MAQOLAT: Journal of Islamic Studies, 2025)
Islamic Religious Education learning in majelis taklim plays a strategic role in shaping the character and spirituality of the Muslim community. However, the effectiveness of this learning process still faces challenges, particularly in the development of comprehensive and applicable teaching materials. The materials delivered are often textual and theoretical, lacking contextual relevance and failing to accommodate the diverse needs of participants. This study aims to develop a concept for Islamic Religious Education learning materials through a holistic-integralistic approach that encompasses cognitive, affective, and psychomotor aspects. The research methodology employed includes a literature review and observations of several majelis taklim. The holistic-integralistic approach is implemented through a systematic instructional design framework known as the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation. This model is applied by incorporating andragogical principles and considering socio-cultural aspects. The findings indicate that this approach fosters a more meaningful and applicable learning experience. Additionally, the delivery of teaching materials becomes more contextual, aligning with the needs of learners and the challenges of modern life.